2022
DOI: 10.3390/su14095273
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Analysis, Implications, and Effects of the Teleworking System in Romania

Abstract: The COVID-19 pandemic is a mobilizing circumstance for rethinking the economic activities of companies, as well as reorganizing the way employees work. To comply with the regulations imposed worldwide, most economic activities were transferred to the online environment. The purpose of the paper is to carry out an investigation of the Romanian telework system implemented during the pandemic based on the perception of employees and employers. Our research was conducted based on an online opinion poll in which 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…It is to be noted how new ideas were created through repeated messages [47]. However, as the situation stabilized, companies and employees were able to better understand the benefits and challenges brought by telework, and studies moved toward analyzing results concerning sustainability, stressing the necessity of issuing policies to decrease the main risks, and offering practical perspectives for teleworkers and managers [48][49][50].…”
Section: Literature Review 21 Contextualizationmentioning
confidence: 99%
“…It is to be noted how new ideas were created through repeated messages [47]. However, as the situation stabilized, companies and employees were able to better understand the benefits and challenges brought by telework, and studies moved toward analyzing results concerning sustainability, stressing the necessity of issuing policies to decrease the main risks, and offering practical perspectives for teleworkers and managers [48][49][50].…”
Section: Literature Review 21 Contextualizationmentioning
confidence: 99%
“…Digital transformation received a fast push due to the pandemic. For instance, the teleworking system in Romania was implemented during the pandemic [11]. Subsequently, adopting and integrating new digital technologies into the enterprise infrastructure is one of the biggest challenges that companies are currently facing [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that a more relationshiporiented behavior on the managers' side, particularly focused on communication, is crucial for telework implementation, as professional isolation negatively impacts job performance (Golden et al, 2008;Dahlstrom, 2013). Effective supervision, defined as managing results and building proactive communication policies for achieving inclusion and building trusting relationships through communication (Baruch, 2001), as well as the existence of a collaborative relationship (Ionescu et al, 2022) play a significant role in the link between telework arrangements and organizational performance. Pearlson and Saunders (2001) noted the need to focus on teleworkers' results, clear business objectives and measures, frequent and multiple communications, and well-supported infrastructure.…”
mentioning
confidence: 99%